Local Practice of Intelligent Innovation and Sustainable Development of Environmental in NCUT of Taiwan - Wen-Yuan Chen; He-Yau Kang; Win-Jet Luo (Universitas Diponegoro, 2022)
The purpose of this project is to assist local fruit farmers to increase output value through innovative development, build a distribution network for agricultural products, and increase farmers' income. In the technology of increasing agricultural output value, NCUT's professional team applies smart agricultural technology to monitor fruit trees to prevent pests and diseases, maintain the healthy growth and yield of fruit trees, and solve the problem of lack of labor in farmland. The NCUT team practices strategic marketing and business models to guide fruit farmers to promote local creation and enhance local cultural characteristics. This project assists in the implementation of new quality-guaranteed and value-added technologies, promotes high-quality agricultural products across the country and improves local tourism marketing, and activates agricultural product promotion activities to achieve mutual support between industry and academia. In addition, in response to the 50th anniversary of the World Earth Day, NCUT held a tree planting to save the earth to implement the concept of sustainable environmental development. President Chen, faculty and students planted 500 Cinnamomum camphor seedlings on the NCUT campus in response to the UN Climate Change Framework Convention.Keyword: Environmental Protection, Local Practice, Intelligent Innovation, Intelligent Agricultural Technology, Sustainable Development